Quantitation of brain tissue changes associated with white matter hyperintensities by diffusion-weighted and magnetization transfer imaging: The LADIS (leukoaraiosis and disability in the elderly) study - Ropele, Stefan; Seewann, Alexandra; Gouw, Alida A.; van der Flier, Wiesje M.; Schmidt, Reinhold; Pantoni, Leonardo; Inzitari, Domenico; Erkinjuntti, Timo; Scheltens, Philip; Wahlund, Lars O.; Waldemar, Gunhild; Chabriat, Hugues; et al. (Journal of magnetic resonance imaging, 2009)
Purpose To explore the value of diffusion‐weighted imaging (DWI) and magnetization transfer imaging (MTI) for the improved detection and quantification of cerebral tissue changes associated with ageing and white matter hyperintensities (WMH). Materials and Methods DWI (n = 340) and MTI (n = 177) were performed in nine centers of the multinational Leukoaraiosis And DISability (LADIS) study investigating the impact of WMH on 65‐ to 85‐year‐old individuals without prior disability. We assessed the apparent diffusion coefficient (ADC) and magnetization transfer ratio (MTR) of normal appearing brain tissue (NABT) and within WMH and related them to subjects' age and WHM severity according to the Fazekas score. Results ADC and MTR values showed a significant inter‐site variation, which was stronger for the MTR. After z‐transformation multiple regression analysis revealed WMH severity and age as significant predictors of global ADC and MTR changes. Only lesional ADC, but not MTR was related to WMH severity. Conclusion ADC and MTR are both sensitive for age and WMH related changes in NABT. The ADC is more sensitive for tissue changes within WMH and appears to be more robust for multicenter settings. J. Magn. Reson. Imaging 2009;29:268–274. © 2009 Wiley‐Liss, Inc.